Hypermetabolism is an independent prognostic factor of survival in metastatic non-small cell lung cancer patients. Issue 6 (June 2020) - Jouinot, Anne; Ulmann, Guillaume; Vazeille, Clara; Durand, Jean-Philippe; Boudou-Rouquette, Pascaline; Arrondeau, Jennifer; Tlemsani, Camille; Fournel, Ludovic; Alifano, Marco; Wislez, Marie; Chapron, Jeanne; Le Bris, Camille; et al.
Summary: Background & aims: Metastatic non-small cell lung cancer (NSCLC) is the first cause of cancer death worldwide. Increased resting energy expenditure (REE) is frequent among cancer patients and may contribute to cancer cachexia. The aim of this study was to examine the prognostic value of increased REE in metastatic NSCLC patients. Methods: This observational study was conducted between June 2012 and November 2017 in the outpatient unit of the oncology department of Cochin hospital, Paris. Consecutive patients with newly diagnosed stage IV NSCLC underwent measurement of REE by indirect calorimetry before treatment initiation. Uni- and multivariate analysis of overall survival (OS, Cox models) included age, sex, smoking habit, histological subtype, performance status, body mass index, weight loss, albumin and CRP levels and the ratio of measured REE to the REE predicted by the Harris Benedict formula (mREE/pREE). Results: 144 patients were enrolled: mean age 64 years, 63% male, 90% non-squamous carcinoma, including 17% with ALK / EGFR alteration. In univariate analysis, tobacco consumption (p = 0.007), histo-molecular subtype (p < 10 −3 ), performance status (p = 0.04), weight loss (p < 10 −4 ), albumin (p < 10 −4 ), CRP (p = 0.001) and mREE/pREE ratio (>vs ≤ 120%: HR = 2.16, p < 10 −3 ) were significant prognostic factors of OS. Median OS were 6.1 and 17.3 months in patients with mREE/pREE ratio > and ≤120%, respectively. In multivariate analysis, histo-molecular subtype (non-squamous ALK / EGFR mutated vs squamous carcinoma: HR = 0.25, p = 0.006), weight loss (>vs ≤ 5%: HR = 1.98, p = 0.004), albumin (≥vs < 35 g/L: HR = 0.56, p = 0.02) and mREE/pREE ratio (> vs ≤120%: HR = 1.90, p = 0.004) were identified as independent prognostic factors. Conclusions: Elevated resting energy expenditure emerges as an independent prognostic factor in metastatic NSCLC.